Sources of work stress in veterinary practice in the UK. (11th May 2019) - O'Connor, Elinor
Abstract : The veterinary profession recognises the importance of addressing work‐related stress for veterinary surgeons' wellbeing. Identifying aspects of veterinarians' work that are sources of stress is a key step in implementing appropriate stress management interventions for the profession. However, little systematic research on the causes of stress in veterinary work has been carried out. A qualitative interview study was conducted with 18 veterinarians practising in the UK to explore aspects of their work that are stressful. Thematic analysis revealed principal stressors to be poor work‐life balance, interaction with animal owners, specific aspects of euthanasia, dealing with poor animal welfare and staff management responsibilities. Injury risk, supervision arrangements for newly qualified veterinarians and lack of control over work were stressors for some. The practical implications of the findings for stress management in veterinary work are considered. Comments by several participants indicated a strong achievement focus and possible perfectionism. It is proposed that veterinarians with perfectionist traits might experience greater psychological distress in the face of some specific stressors in veterinary practice, and further investigation of possible interactive effects of work stressors and perfectionism on veterinarians' wellbeing is merited.